Supplier relationship marketing practices and small retailer performance in South Africa - KM Makhitha (Cogent Business & Management, 2019)
The purpose of the study on which this article is based, was to interrogate the relationship marketing practices of small retailers in South Africa. The researcher also explores the impact of relationship marketing practices on the performance of small retailers in South Africa (SA). Objectives were formulated and hypotheses were tested using ANOVA and regression analysis and survey data drawn from small retailers’ owners/managers in South Africa. The results indicate that small retailers in SA practice relationships marketing and that they share information with suppliers and are involved in various types of relationships such as ling-term relationships, collaborative relationships and transactional relationships. Information sharing was found to influence the performance of small retailers while other relationship types did not. Moreover, the age of the owners of small enterprises did not influence their relationship marketing practices, while their level of education was found to do so. This study offers managerial insights into the roles that relationship marketing, especially information sharing with their suppliers play in the performance of small retailers. This study makes three key contributions. First, the study proved that small retailers practice relationship marketing, although they still emphasise transactional relationships over collaborative relationships. Second, the importance of information sharing in small retailers, which requires that small retailers continue sharing information for improved business performance. Third, the demographics of small business owners/managers have no influence on relationship marketing practices.